Management of Neurologic Complications in Patients with Brain and Spine Tumors - V. Bonm, Alipi; Taylor, Lynne P. (Seminars in Neurology, 2024)
Patients with brain and spine tumors represent a distinct population with unique needs. We provide a practical review of neurologic care in this group with an emphasis on familiarizing the general neurologist to the nuances of neuro-oncologic supportive care. We review the management of cerebral edema, steroid dosing, and pertinent side effects. We discuss seizure management, including choice of anticonvulsants, putative antitumor effects, and important seizure mimics like drop attacks. We review the presentation and symptomatology of stroke-like migraine attack after radiation therapy (SMART syndrome). We describe the signs and symptoms that should prompt concern for metastatic spinal cord compression, as well as both acute and definitive treatment options. Finally, we discuss the underappreciated incidence of venous thromboembolic events, particularly in patients with gliomas, and review the data on management.
Keywords: steroids; seizures; headache; neurologic complications; cerebral edema